Proteomic profile of the antibody diversity in circulating extracellular vesicles of lung adenocarcinoma - Xinfu Huang; Lijuan Xiong; Yang Zhang; Xin Peng; Hongping Ba; Peng Yang (Scientific Reports)
Abstract Immunoglobulin diversity encompasses B-cell receptor, T-cell receptor, and antibody diversity. Existing studies have focused more on the role of B-cell and T-cell receptor diversity in tumor immunity, while the role of antibody diversity is less understood. This study examined and compared the blood extracellular vesicles (EVs) of lung cancer patients and healthy individuals using proteomics and bioinformatics analyses. The results revealed that among the 270 identified proteins, those involved in defense mechanisms were the most abundant. Most of these were antibody subtypes, accounting for 50.00%. Similarly, of the 40 identified EVs differentially expressed proteins (DEPs), 29 were involved in defense mechanisms (72.50%), with a higher proportion being antibody subtypes (82.76%). Furthermore, 24 DEP antibody subtypes were implicated in 18 immune reaction-related signaling pathways. These findings suggest that human serum EVs contain a significant number of antibody subtypes, and the antibody subtypes from lung cancer serum EVs differ from those of healthy controls (HCs). The variations in antibody diversity may be closely associated with lung cancer tumor immunity.